Placental Malaria: A New Insight into the Pathophysiology - Sharma, Lalita; Shukla, Geeta (Frontiers in Medicine, 2017)
Malaria in pregnancy poses a great health risk to mother and her fetus and results into complications like abortion, still birth, intra uterine growth retardation and low birth weight. The heavy infiltration of Plasmodium falciparum infected RBCs in the intervillous spaces of placenta seems to be responsible for all the complications observed. Infected RBCs in the placenta cause an inflammatory environment with increase in inflammatory cells and cytokines which is deleterious to the placenta. Increased inflammatory responses in the infected placenta results into oxidative stress which in turn cause oxidative stress induced placental cell death. Moreover, heat shock proteins which are produced in high concentration in stressed cells to combat the stress have been reported in fewer concentrations in malaria infected placenta. Pathologies associated with placental malaria seems to be effect of a change in immune status from antibody mediated immune response to cell mediated immune response resulting into excess inflammation, oxidative stress, apoptosis and decreased heat shock protein expression. However, we also need to study other aspects of pathologies so that better drugs can be designed with new molecular targets.